Use of induced sputum cell counts to investigate airway inflammation in asthma. Issue 1 (January 1992) - Pin, I; Gibson, P G; Kolendowicz, R; Girgis-Gabardo, A; Denburg, J A; Hargreave, F E; Dolovich, J
Abstract : BACKGROUND: Airway inflammation is considered to be important in asthma but is relatively inaccessible to study. Less invasive methods of obtaining sputum from patients unable to produce it spontaneously should provide a useful investigational tool in asthma. METHODS: A method to induce sputum with inhaled hypertonic saline was modified for use in 17 asthmatic patients and 17 normal subjects who could not produce sputum spontaneously. The success rate and safety of the method, the reproducibility of cell counts, and differences in cell counts between the asthmatic and normal groups were examined. Hypertonic saline solution 3-5% was inhaled for up to 30 minutes after inhalation of salbutamol. Subjects were asked to expectorate sputum every five minutes. The quality of the sample was scored on the volume of plugs and the extent of salivary contamination. Plugs from the lower respiratory tract were selected for a total cell count and for differential cell counts of eosinophils and metachromatic cells (mast cells and basophils) in direct smears. RESULTS: Adequate samples from the lower respiratory tract were obtained in 76% of first attempts. The mean fall in the forced expiratory volume in one second (FEV1) during inhalation of saline was 5.3% and the maximum fall 20%. Eosinophil and metachromatic cell counts were reproducible (reliability coefficient 0.8 and 0.7 respectively). When compared with sputum from normal subjects sputum from asthmatic patients contained a significantly higher proportion of eosinophils (mean 18.5% (SE 3.8%) v 1.9% (0.6%)) and metachromatic cells (0.50% (0.18%) v 0.039% (0.014%)). In the asthmatic group the differential eosinophil count correlated with the baseline FEV1. CONCLUSION: Induced sputum is capable of detecting differences in cell counts between normal and asthmatic subjects and merits further development as a potential means of assessing airway inflammation in asthma.